2017
DOI: 10.1534/g3.117.300076
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction Within and Across Biparental Families: Means and Variances of Prediction Accuracy and Usefulness of Deterministic Equations

Abstract: A major application of genomic prediction (GP) in plant breeding is the identification of superior inbred lines within families derived from biparental crosses. When models for various traits were trained within related or unrelated biparental families (BPFs), experimental studies found substantial variation in prediction accuracy (PA), but little is known about the underlying factors. We used SNP marker genotypes of inbred lines from either elite germplasm or landraces of maize (Zea mays L.) as parents to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 58 publications
(136 reference statements)
7
37
0
Order By: Relevance
“…Averaged across the four DHL, there was considerable variation in r among traits (Table 2). Such variation was also observed among segregating biparental populations in experiments with maize (Lehermeier et al 2014;Lian et al 2014) and in simulations (Schopp et al 2017b). A possible explanation is that each trait has a different genetic architecture, so that covariances among individuals estimated by genomewide markers may not equally well reflect the conditions at the underlying QTL.…”
Section: Variation In the Prediction Accuracy Among Traitsmentioning
confidence: 79%
See 4 more Smart Citations
“…Averaged across the four DHL, there was considerable variation in r among traits (Table 2). Such variation was also observed among segregating biparental populations in experiments with maize (Lehermeier et al 2014;Lian et al 2014) and in simulations (Schopp et al 2017b). A possible explanation is that each trait has a different genetic architecture, so that covariances among individuals estimated by genomewide markers may not equally well reflect the conditions at the underlying QTL.…”
Section: Variation In the Prediction Accuracy Among Traitsmentioning
confidence: 79%
“…However, no pattern could be recognized between the LPS of pairwise combinations of DHL and the observed r because means of r were quite low, and there was a large variation of r for different combinations of TS/PS and traits (Table 3). In predictions across unrelated biparental families (Schopp et al 2017b), the LPS was only loosely correlated with the prediction accuracy, whereas the parameter u ii * , referring to the proportion of polymorphic markers between two DHL, was much more important. However, in our study, we observed no association between u ii * ( Figure S4) and r.…”
Section: Gp Between Dhl From Landracesmentioning
confidence: 94%
See 3 more Smart Citations